Use of PCR in resolving diagnostic difficulties potentially caused by genetic variation of hepatitis B virus. Issue 2 (February 1998) - van Deursen, F J; Hino, K; Wyatt, D; Molyneaux, P; Yates, P; Wallace, L A; Dow, B C; Carman, W F
Abstract : AIMS: To assess the relevance of genetic variants of hepatitis B virus (HBV) and to demonstrate the usefulness of the polymerase chain reaction (PCR) in cases of HBV diagnostic difficulty. METHODS: Five serum samples from patients that presented diagnostic difficulty in routine laboratories were sent to a research laboratory for PCR, and if appropriate, S gene sequencing, in vitro expression, and antigenic analysis. RESULTS: The demonstration of HBV in serum by PCR allowed a definitive diagnosis of current infection. One serum sample with poor reactivity in a diagnostic assay had a minor hepatitis B surface antigen (HBsAg) variant and another with very poor reactivity had multiple variants of HBsAg. Transient HBsAg reactivity was observed in a recently vaccinated patient. A hepatitis Be antigen (HBeAg) false positive reaction was noted in a patient from a well defined risk group for HBV. One patient who was strongly HBsAg/HBeAg positive, but anti-hepatitis B core antibody negative, was viraemic. CONCLUSIONS: PCR may become the gold standard for the diagnosis of current HBV infection. HBV variants are responsible for a proportion of diagnostically difficult cases. Modification of commercial assays is necessary to increase the sensitivity of detection of such variants.